Threats, Victims, and Survivors: The Racialized Gendering of Syrian Refugees and Literary Contestations of Dominant Media Narratives - Nayrouz, Yasmin (Refuge, 2024)
Western media narratives about Syrian refugees frequently depict men as threats and women as helpless victims through racialized and gendered constructions. Contemporary Syrian diasporic literature can counter these problematic and dominant media portrayals. Specifically, Christy Lefteri’s The Beekeeper of Aleppo and Atia Abawi’s A Land of Permanent Goodbyes offer readers opportunities to empathize by contesting racialized representations of Syrian refugee men as threats by positively characterizing complex male protagonists, revealing their vulnerabilities, and emphasizing their care for their families—especially for the women in their families. They acknowledge the patriarchal cultural expectations for Syrians and reaffirm the agency and power of refugee women’s voices by showing their effects on others’ empathy.